Beginning Java$1!" (BEE 6 Platform with GlassFish$1!" (B3s - Goncalves, Antonio; SpringerLink (Online service) (Berkeley, CA : Apress, 2010)
Java Enterprise Edition (Java EE) continues to be one of the leading Java technologies and platforms from Oracle (previously Sun). Beginning Java EE 6 Platform with GlassFish 3, Second Edition is this first tutorial book on the final version of the Java EE 6 Platform. Step by step and easy to follow, this book describes many of the Java EE 6 specifications and reference implementations, and shows them in action using practical examples. This book uses the new version of GlassFish 3 to deploy and administer the code examples. Written by an expert member of the Java EE 6 specification request and review board in the Java Community Process (JCP), this book contains the best information possible, from an expert$1 (Bs perspective on enterprise Java technologies.s
Java EE 6 at a Glance -- Java Persistence -- Object-Relational Mapping -- Managing Persistent Objects -- Callbacks and Listeners -- Enterprise Java Beans -- Session Beans and the Timer Service -- Callbacks and Interceptors -- Transactions and Security -- JavaServer Faces -- Pages and Components -- Processing and Navigation -- Sending Messages -- SOAP Web Services -- RESTful Web Services.
Keywords: Computer science; Computer Science; Programming Techniques